Factors influencing the relationship between cochlear health measures and speech recognition in cochlear implant users - Ladan Zamaninezhad; Berkutay Mert; Heval Benav; Jochen Tillein; Carolyn Garnham; Uwe Baumann (Frontiers in Integrative Neuroscience, 2023)
BackgroundOne factor which influences the speech intelligibility of cochlear implant (CI) users is the number and the extent of the functionality of spiral ganglion neurons (SGNs), referred to as “cochlear health.” To explain the interindividual variability in speech perception of CI users, a clinically applicable estimate of cochlear health could be insightful. The change in the slope of the electrically evoked compound action potentials (eCAP), amplitude growth function (AGF) as a response to increased interphase gap (IPG) (IPGEslope) has been introduced as a potential measure of cochlear health. Although this measure has been widely used in research, its relationship to other parameters requires further investigation.MethodsThis study investigated the relationship between IPGEslope, demographics and speech intelligibility by (1) considering the relative importance of each frequency band to speech perception, and (2) investigating the effect of the stimulus polarity of the stimulating pulse. The eCAPs were measured in three different conditions: (1) Forward masking with anodic-leading (FMA) pulse, (2) Forward masking with cathodic-leading (FMC) pulse, and (3) with alternating polarity (AP). This allowed the investigation of the effect of polarity on the diagnosis of cochlear health. For an accurate investigation of the correlation between IPGEslope and speech intelligibility, a weighting function was applied to the measured IPGEslopes on each electrode in the array to consider the relative importance of each frequency band for speech perception. A weighted Pearson correlation analysis was also applied to compensate for the effect of missing data by giving higher weights to the ears with more successful IPGEslope measurements.ResultsA significant correlation was observed between IPGEslope and speech perception in both quiet and noise for between-subject data especially when the relative importance of frequency bands was considered. A strong and significant correlation was also observed between IPGEslope and age when stimulation was performed with cathodic-leading pulses but not for the anodic-leading pulse condition.ConclusionBased on the outcome of this study it can be concluded that IPGEslope has potential as a relevant clinical measure indicative of cochlear health and its relationship to speech intelligibility. The polarity of the stimulating pulse could influence the diagnostic potential of IPGEslope.